Avaliação da dor de crianças submetidas a anestesia local odontológica com seringa convencional e com seringa controlada por computador - Pereira, Mirella de Sousa (2014)
ABSTRACT The pain is mult ifatorial phenomenon and it can have psychological and cultural nature. Studies have related that local anesthesia used in Denti stry is the greatest cause of pain and anxiety for the patients in the dental office. The aim of this study was to evaluate the child pain - related who received local anesthesia, delivered by a conventional syringe and a syringe controlled by computer. Thir ty children aged 7 – 12 years attended two clinical sessions and received two local anesthesias : with conventional syringe and syringe controlled by computer. Only one researcher carried out the anesthesia procedures, and those consisted buccal infiltration to anesthetize maxillary molars. Pain and discomfort were analyzed by scales: Facial Anxiety Scale (FAS), Sound, Eyes and Motor Scale (SEM), Visual Analogue Scale (VAS), Frankl Scale and e Child Fear Survey Schedule Dental Subscale (CFSS - DS). The scales we re applied in specific moments, before, during and after the anesthesia. After the second clinical session, the child was asked if she preferred to be anesthetized with conventional syringe or syringe controlled by computer. We observed that syringe contro lled by computer was less uncomfortable and painful. The re was a significantly difference between F AS and SEM scales and that 100% of children in the SEM scale, showed grade 1 (comfort) when using the device, and with the anesthetic syringe exhibited grade 1 (comfort - 73.3%), 2 (mild discomfort - 16.6%) and 3 (moderate pain - 10%). More than half of children (73.3%) reported a preference of anesthesia with computer - controlled syringe . We concluded the performance characteristics of the com puter - controlled anesthesia didn’t modify the child's behavior after application, demonstrating a minimum of discomfort and pain, showing better resul ts than anesthesia using conventional syringe.